PTU-079 The Inflammatory Bowel Disease Quality Improvement Project – Progress Two Years on. (4th June 2013) - Shaw, I; Fernandez, E
Abstract : Introduction: The IBD Quality Improvement Project (IBDQIP) was established in 2010, as a project to help improve adult and paediatric IBD services across the UK. Here we report the first two years of progress. Methods: IBDQIP uses a web-based system (www.ibdqip.co.uk ) to enable services to benchmark themselves against the national IBD standards and then action plan improvement using a combination of self-assessment, network support and a shared repository of best practise. Results are provided to sites graphically as a performance dashboard using a hierarchical grading system. Initial sites completed the first assessment in 2011, with a second round in 2012. Progress has been assessed by comparing scores between rounds and from site feedback. Results: Participation increased over time, with 69 sites (56 adult & 13 paediatric) participating in round 1 (2011) and 84 sites (66 adult & 18 paediatric) in round 2 (2012). 90% of sites completed their evaluation within 4 hours (median 2–3). 60% of sites met as an MDT to complete their return, which was rated as the most powerful catalyst for change (figure 1 ). Significant improvement has been made across a range of measures: Conclusion: In it's first two years, IBDQIP has shown increased participation and has proved to be a rapid and effective tool to improve IBD services. The project has now merged with the National IBD Audit and will be rolled out to all IBD services in 2014. Disclosure of Interest: None Declared